Corneal Emergencies - Sharma, Bhavana; Titiyal, Jeewan S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book provides a comprehensive insight into various corneal emergencies along with their risk factors, causative agents, diagnostic pearls, treatment challenges and management options. It provides essential information on relevant anatomical and physiological aspects in addition to epidemiology and risk factors. Comprising of explanatory flow diagrams, diagnostic and treatment algorithms and high-quality illustrations, this book is written and edited by renowned corneal specialists who have come together to address this complex topic in a simple and effective manner. The book highlights an important aspect of cornea which is relevant for specialists and general ophthalmologists alike and also serves as an important resource for postgraduate students and trainees. It emphasizes on the practical management of corneal emergencies, supplemented with preferred practice patterns and guidelines. Additionally, the book serves as a quick reference for ophthalmic practitioners to adequately manage such cases at the point of first contact.
Anatomical and physiological aspects in emergencies of cornea -- Epidemiology and risk factors -- Requisites of operation room and cornea clinic to manage corneal emergencies -- Diagnostic and therapeutic approach in management of corneal emergencies -- Minor corneal emergencies -- Mechanical injuries of cornea -- Microbial keratitis -- Perforations in corneal ulcer -- Complications after refractive surgeries -- Chemical injuries -- Corneal emergencies after penetrating and lamellar keratoplasty -- Graft rejection -- Corneal wound dehiscence after surgery -- Approach to management -- Corneal emergencies in contact lens users -- Immune mediated peripheral ulcerative keratitis -- Emergencies associated with advanced corneal ectasias -- Preventive aspects and public awareness.
Keywords: Ophthalmology; Ophthalmology; Corneal Diseases -- therapy; Emergency Treatment -- methods; Emergencies